Aqueous Two-Phase Systems: A New Approach for the Determination of Brilliant Blue FCF in Water and Food Samples - Sabah Shiri; Tahere Khezeli; Shahram Lotfi; Sina Shiri (Journal of Chemistry)
A novel, simple, and more sensitive spectrophotometric procedure has been developed for the determination of brilliant blue FCF in water and food samples by an aqueous two-phase system (ATPS). In this method, adequate amount of polyethylene glycol/ sodium carbonate (PEG-4000/Na2CO3) was added to aqueous solution for formation of a homogeneous solution. To the mixture solution, suitable amount of Na2CO3 was added, the mixture solution was shaken until the salt was dissolved, and then it was separated into two clear phases easily and rapidly. The target analyte in the water sample was extracted into the polyethylene glycol phase. After extraction, measuring the absorbance at 634 nm was done. The effects of different parameters such as polyethylene glycol (type and concentration), pH, salt (type and amount), centrifuge time, and temperature on the ATPS of dye was investigated and optimum conditions were established. Linear calibration curves were obtained in the range of 0.25–750 ng/mL for brilliant blue FCF under optimum conditions. Detection limit based on three times the standard deviation of the blank (3Sb) was 0.12 ng/mL. The relative standard deviation (RSD) for 400 ng/mL was 3.14%. The method was successfully applied to the determination of brilliant blue FCF in spiked samples with satisfactory results. The relative recovery was between 96.0 and 102.2%.